Prevalência de lesões epiteliais penianas e infecção pelo papilomavírus humano (HPV) em parceiros de mulheres com lesões epiteliais cervicais - Dias, Julia Maria Goncalves (2013)
OBJECTIVES: To determine the association of epithelial lesions and penile Human Papillomavirus infection among women with Human Papillomavirus induced cervical epithelial lesions and their partners.METHODS: To obtain the answer to the objectives were developed two studies. The first cross- sectional with 82 partners of women with cervical lesions Human Papillomavirus induced, examined by peniscopy, cytology and genotyping. The second study a systematic review with meta-analysis. The authors collected published information in databases about the prevalence of penile epithelial lesions and explored potential associations in partners of women with HPV-induced lesions. For the analysis we used methodological standards STROBE Initiative. Additionally meta-analyzes were conducted involving the selected studies.RESULTS: Observed positive peniscopy in 100% of patients. Koilocytosis in76.8%, and viral DNA positive in 14%, Human Papillomavirus types found were 16, 31 and 33. There was a significant association between the presence of penile injury and the time of contact with the partner p = 0.02. The authors included 29 studies in systematic review with a total of 8033 patients. Studies of case-control showed better methodological quality assessment in STROBE (Strengthening the Reporting of Observational Studies in Epidemiology). All patients were included in the meta-analyzes. There was a positive association between the detection methods for HPV and peniscopy among partners of women with cervical lesions and HPV infection in cross-sectional studies with Relative Risk (RR) of 0.87 and 0.34, and case-control (RR 0.13 and 0.58). The association was negative among cohort studies (RR 2.41 and 1.40).CONCLUSION: Positive peniscopy prevalence was higher than those found in the literature. There was significant association between penile lesion and time for socializing, in detriment of other risk variables A significant positive association in the meta-analysis of cross-sectional studies and case-control seems to demonstrate that there is a positive risk to partner of the woman s cervical lesion also acquires viral infection. The relative risk observed in the search for associations between HPV infection and peniscopy with both, positive and negative results appeared as a protective factor for acquiring HPV induced lesions in man. These tests could represent preventive methods for acquiring viral infection.